Pain profile and opioid medication use in patients with idiopathic inflammatory myopathies. (17th May 2022) - Bhashyam, Abhiram; Lubinus, Manuel; Filmore, Emily; Wilson, Lynn; Williams, Jerry; Gonzalez Ramos, Osniel; Bhai, Salman
Abstract: Objectives: Pain is commonly reported in people living with myositis. This study assesses the presence of pain in the subtypes of myositis as well as the frequency of opioid and non-opioid pain medication use. Methods: A survey was developed and distributed by Myositis Support and Understanding, a patient-led advocacy organization, to members of its group. Multivariate logistic regression analysis and chi-squared tests were performed. Results: A total of 468 participants completed the survey. A total of 423 participants (DM n = 183, PM n = 109 and IBM n = 131) were included, based on reported diagnosis, for final analysis. Some 91.5% of myositis participants reported current or past pain, with 99% attributing their pain to myositis. There was a lower likelihood of pain in participants aged >60 years [odds ratio (OR) 0.2, 95% confidence interval (CI) 0.1, 0.6, P = 0.003]. The percentage of participants reporting pain was statistically different based on myositis type (DM 97.2%, IBM 80.9% and PM 94.5%, P < 0.001), with a higher likelihood of pain in DM compared with IBM (OR 3.7, 95% CI 1.3, 10.2, P = 0.011). There was a lower likelihood of pain in participants aged >60 years (OR 0.2, 95% CI 0.1, 0.6, P = 0.003). Of the 387 participants reporting pain, 335 reported using pain medications (69% prescribed opioids). Male sex, age >60 years and myositis subtype were not associated with likelihood of non-opioid use. Conclusion: Pain is a commonly reported symptom in myositis with variable treatment strategies, including opioid medications. This study highlights the importance of addressing pain as part of myositis treatment as well as the need for future studies understanding treatment effectiveness.